N-Ethyl-3,5-dinitrobenzamide - Xu, Jia-Ying (International Union of Crystallography, 2011)
In the title molecule, C(9)H(9)N(3)O(5), the dihedral angle between the mean planes of the amide group and the benzene ring is 31.24 (14)°. In the crystal, N—H⋯O hydrogen bonds link the molecules to form one-dimensional chains propagating in [100].